2014
DOI: 10.1021/ja5049626
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Effect at Protein/Graphene Interface: A Bioinspired Perspective To Understand Amyloid Formation

Abstract: Protein misfolding to form amyloid aggregates is the main cause of neurodegenerative diseases. While it has been widely acknowledged that amyloid formation in vivo is highly associated with molecular surfaces, particularly biological membranes, how their intrinsic features, for example, chirality, influence this process still remains unclear. Here we use cysteine enantiomer modified graphene oxide (GO) as a model to show that surface chirality strongly influences this process. We report that R-cysteine modific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 75 publications
3
79
0
Order By: Relevance
“…From the insights of bionics, many compelling studies have shown the effect of chirality on the protein adsorption process [94,95,96] and even on cell behaviors [97,98]. In 2014, Sun et al showed that surface chirality might strongly influence the aggregation of A β (1–40) (Figure 6a) [41]. Utilizing cysteine (Cys) enantiomer-modified graphene oxide (GO) as a model platform, they monitored the amyloid formation process through ThT fluorescence spectroscopy and AFM.…”
Section: Protein Aggregation Modulated By Chiral Interfacementioning
confidence: 99%
See 3 more Smart Citations
“…From the insights of bionics, many compelling studies have shown the effect of chirality on the protein adsorption process [94,95,96] and even on cell behaviors [97,98]. In 2014, Sun et al showed that surface chirality might strongly influence the aggregation of A β (1–40) (Figure 6a) [41]. Utilizing cysteine (Cys) enantiomer-modified graphene oxide (GO) as a model platform, they monitored the amyloid formation process through ThT fluorescence spectroscopy and AFM.…”
Section: Protein Aggregation Modulated By Chiral Interfacementioning
confidence: 99%
“…Therefore, simplified interfaces such as or peptide- or amino acid-modified surfaces may be the ideal platform for further investigation. As described in Section 4, Sun et al [41,100] designed diverse chiral amino acid-modified surfaces and proposed the critical role of surface stereoselective interaction in A β aggregation. Lequin and Ongeri [116] designed a novel class of peptidomimetics composed of two hydrophobic dipeptides (Ala-Val and Val-Leu) linked to a d -glucopyranosyl scaffold.…”
Section: Protein Aggregation Modulated By Biomolecules and Their Imentioning
confidence: 99%
See 2 more Smart Citations
“…For example, adsorption of nucleotides, nucleic acids, and proteins by GO was reported. [22][23][24] In this work, we employed ITC to study the adsorption between liposomes and GO.…”
Section: Introductionmentioning
confidence: 99%